Case report: Conversion therapy to permit resection of initially unresectable hepatocellular carcinoma - Chen, Kang; Luo, Cheng-Piao; Ge, De-Xiang; Wang, Ke-Lin; Luo, Qin; Li, Yan-Zhi; You, Xue-Mei; Xiang, Bang-De; Li, Le-Qun; Ma, Liang; Zhong, Jian-Hong (Frontiers in Oncology, 2022)
Most patients with hepatocellular carcinoma (HCC) are diagnosed when the disease is already at an advanced stage, so they are not eligible for resection and their prognosis is poor. The combination of transarterial chemoembolization (TACE) with immune checkpoint inhibitors or tyrosine kinase inhibitors can improve unresectable HCC to the point that patients can be treated with surgery. Here we describe two cases of such “conversion therapy”. One patient was a 52-year-old man in Child-Pugh class A with treatment-naive HCC whose 11.3-cm tumor had invaded the middle hepatic vein and right branch of the portal vein. He was treated with TACE plus camrelizumab, and radical resection was performed 3 months later. No evidence of recurrence was observed during 5-month follow-up. The other patient was a 42-year-old man in Child-Pugh class A with HCC involving a 11.4-cm tumor and severe liver cirrhosis. The patient was treated with TACE and lenvatinib, but the embolic effect after one month was unsatisfactory, so the regional treatment was changed to hepatic artery infusion chemotherapy and transcatheter arterial embolization. Radical resection was performed 2 months later, and no recurrence was evident at 1-month follow-up. These cases demonstrate two conversion therapies that may allow patients with initially unresectable HCC to benefit from resection.